Pilot Study of Hypnotic Relaxation Therapy for Well-Being (HRT-WB): A New Intervention to Enhance Well-Being and Positive Affect. Issue 4 (2nd October 2022) - Na, Hyeji; Ekanayake, Vindhya; Padilla, Victor; Elkins, Gary R.
ABSTRACT: The purpose of this study was to investigate the feasibility, acceptability, and potential effect of a novel hypnotherapeutic intervention, informed by positive psychology, to enhance well-being in college students. The present study investigated adapting hypnotic relaxation therapy for enhancing well-being (denoted as HRT-WB). Twenty-seven college students were enrolled in a 5-week intervention of HRT-WB and instructed in daily home practice of HRT-WB self-hypnosis using audio recordings. Participants completed baseline and endpoint measures of well-being and symptoms of psychological distress. Results showed participants who received the HRT-WB intervention experienced improvements in subjective well-being as well as reductions in psychological distress. At endpoint, 71% of the participants who completed the HRT-WB intervention were categorized as experiencing high levels of well-being, or flourishing. In addition, HRT-WB is a feasible intervention, with high rates of retention, compliance with home practice, and satisfaction. Based on these promising results, further research into HRT-WB is warranted. HRT-WB could be a well-accepted, easily administered, and effective means of addressing well-being and enhancing flourishing.